Factors associated with medical students’ career choices at a private university: a cross-sectional study - Sana Saeed; Mahanoor Raza; Areeba Hussain; Muhammad Maisam Ali; Farah Khalid (Journal of the Pakistan Medical Association, 2023)
This study aimed to identify the factors associated with students’ career choices and the decision whether they wanted to be trained abroad or in Pakistan. The study utilised a cross-sectional design and was conducted between July 2021 and February 2022. An anonymous survey was distributed among the medical students at Aga Khan University, Karachi, Pakistan. All analysis was carried out using Stata 17. A total of 269 students participated in the study. The most sought-after specialties were surgery 68 (25.3%), medicine 25(9.3%), and paediatrics 14(5.2%), and the decision was highly influenced by positive mentors and lifestyle. In addition, 259 (96%) of the students expressed a desire to practice abroad for training due to higher financial prospects and quality of training. This study revealed that providing enthusiastic mentors may encourage medical students to pursue a broader range of specialties. —Continue